Use of Fine-Grained Heat-Strengthened Steels to Increase the Operation Qualities of Bunker Capacities from Thin-Walled Galvanized Profiles - Hezentsvei, Y. I; Bannikov, D. O. (Science and Transport Progress, 2021)
Purpose. The work is aimed to study the use efficiency of fine-grained heat-strengthened steels (mainly 10G2FB) for steel bunker capacities. At the same time, the structural scheme of such a structure using corrugated steel sheets is considered as the main variant. Methodology. To achieve this purpose, a series of numerical calculations was carried out for a steel bunker capacity of a pyramidal-prismatic type with overall dimensions in plan view of 6×5.2 m and a total height of 4.5 m. The capacity was designed for complicated working conditions, in particular, increased loads, including long-term dynamic ones. The potential possibility of operating the container under conditions of high or low temperatures was also taken into account. At the same time, both the traditional structural scheme of a bunker capacity with horizontal stiffening ribs and the developed structural scheme based on corrugated steel sheets were analyzed. The calculations were carried out by the finite element method based on the SCAD for Windows project complex. Findings. Based on the results of the analysis and comparison of the data obtained in numerical calculations, it was found that the use of fine-grained heat-strengthened high-strength steels (for example, steel 10G2FB) for bunker capacities, both the traditional structural scheme with stiffening ribs and the developed structural scheme based on corrugated sheets, allows reducing material consumption by about 30% in both cases. At the same time, due to the good performance of fine-grained heat-strengthened steel 10G2FB, both at high and at low temperatures, it can be effectively used for steel bunker capacities that work in difficult conditions. Originality. The possibility and efficiency of the use of fine-grained, heat-strengthened high-strength steels for the construction of a steel bunker capacity is estimated. At the same time, such an estimation was given not only for structures of the traditional structural scheme with horizontal stiffening ribs, but also for bunkers with a developed structural scheme based on corrugated sheets. Practical value. From a practical point of view, quantitative parameters of the stress-strain state were obtained during investigations of various design variants for a steel bunker capacity. The data are presented in a compact form that is easy to evaluate and compare. They allow us to state about the improvement of the operation characteristics of capacities and the potential reduction of the risks of their failures and accidents during operation.